Identification of Fasciola Species Isolates from Nghe An Province, Vietnam, Based on ITS1 Sequence of Ribosomal DNA Using a Simple PCR-RFLP Method - Do Ngoc Anh; Le Tran Anh; Le Quoc Tuan; Nguyen Duy Bac; Tran Viet Tien; Vu Thi Binh Phuong; Tran Thanh Duong; Nguyen Khac Luc; Nguyen Ba Quang (Journal of Parasitology Research)
Fascioliasis—a disease caused by Fasciola spp. (Platyhelminthes: Trematoda: Digenea)—is considered as the most important helminthic infection of bovine, sheep, and buffalo in Vietnam. The aim of this study is to detect the genotype of Fasciola spp. isolated from bovine and buffalo in the Nghe An province, central Vietnam, using PCR-RFLP and sequence analysis of the first nuclear ribosomal internal transcribed spacer (ITS1). Adult Fasciola spp. were isolated from bile ducts of bovine and buffalo in Nghe An province, Vietnam. Overall, 96 adult flukes from livers of slaughtered animals were collected from abattoirs of different areas. They included 7 samples from infected bovine and 89 samples from infected buffalo. 96/96 samples were identified as Fasciola species by ITS1 of rDNA. In this study, a PCR-RFLP method was used to distinguish between F. hepatica and F. gigantica in ITS1 of rDNA (680 bp) with RsaI restriction enzyme. RFLP pattern with RsaI produced a consistent pattern of 360, 100, and 60 bp fragments in F. hepatica, whereas F. gigantica worms had a profile of 360, 170, and 60 bp in size, respectively. The results showed that using PCR-RFLP based on the first internal transcribed spacers (ITS1) of the ribosomal RNA revealed that 93 out of 96 isolates were of Fasciola gigantica type, whereas three isolates presented an intermediate Fasciola. In the present study, F. gigantica and intermediate form were coexisting in bovine and buffalo in the Nghe An province of central Vietnam, whereas F. hepatica was not detected.